(untitled) - Simmonds, N.W. (London, 1979)
Provides a broad introduction to the principles of plant breeding. Presents a synoptic view of crop history, linking original studies of crop origin and early evolution with recent and possible future trends in breeding. Primarily designed for senior undergraduate and graduate students of agriculture, horticulture, and applied biology.
Keywords: Plant breeding,Crops,Cây trồng; Breeding,Cây giống,Chăn nuôi